Aerospace series. Connector, electrical and optical, rectangular, modular, rectangular inserts, operating temperature 175 °C (or 125 °C) continuous. Locking and polarizing hardware. Product standard Part 201, (30th November 2015) - British Standards Institution
No abstract available